2017
DOI: 10.1186/s13048-017-0366-8
|View full text |Cite
|
Sign up to set email alerts
|

A modified and tailored human follicle isolation procedure improves follicle recovery and survival

Abstract: BackgroundOvarian tissue cryopreservation followed by transplantation after cancer remission is the most commonly applied fertility restoration approach in very young girls and women who require immediate cancer therapy. However, clinicians strongly advise against reimplantation of one’s own ovarian tissue when there is a high risk of recurrence after grafting. For these patients, development of an alternative strategy, namely a transplantable artificial ovary, offers future hope of conceiving. The first essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 31 publications
2
46
0
Order By: Relevance
“…Dolmans et al (2008) showed that 5 months after xenografting, human follicles were able to reach the antral stage. Follicle recovery rates in fibrin and decellularized human ovarian matrices after 1 week of xenografting were found to be comparable to those reported for human ovarian tissue in similar grafting experiments (Nisolle et al 2000, Paulini et al 2016, Chiti et al 2017a, Pors et al 2018. Formation of an ovary-like structure, which is necessary for further follicle development, was also demonstrated in several studies (Dolmans et al 2007, Paulini et al 2016, Chiti et al 2017a.…”
Section: Functionality Of the Transplantable Artificial Ovarysupporting
confidence: 75%
See 4 more Smart Citations
“…Dolmans et al (2008) showed that 5 months after xenografting, human follicles were able to reach the antral stage. Follicle recovery rates in fibrin and decellularized human ovarian matrices after 1 week of xenografting were found to be comparable to those reported for human ovarian tissue in similar grafting experiments (Nisolle et al 2000, Paulini et al 2016, Chiti et al 2017a, Pors et al 2018. Formation of an ovary-like structure, which is necessary for further follicle development, was also demonstrated in several studies (Dolmans et al 2007, Paulini et al 2016, Chiti et al 2017a.…”
Section: Functionality Of the Transplantable Artificial Ovarysupporting
confidence: 75%
“…We found that by subjecting the remaining fragments to fresh enzymatic solution every 30 min, we were able to successfully digest any type of ovarian tissue, from the softest to the hardest. This ensured that all the tissue was processed without affecting the quality of the isolated follicles, as demonstrated by our findings after encapsulation in fibrin and xenografting (Chiti et al 2017a). This new protocol allows personalization of ovarian follicle isolation according to individual tissue properties and should be implemented on a case-by-case basis to make best use of precious ovarian follicles and maximize the chances of pregnancy after artificial ovary transplantation.…”
Section: Isolation Of Primordial and Primary Follicles: Quality And Qmentioning
confidence: 78%
See 3 more Smart Citations